Impact of web accessibility barriers on users with a hearing impairment (2015)
Several user tests were carried out on people with a hearing impairment to evaluate the impact of different web accessibility barriers on two similar web sites, one accessible and the other not accessible. The tests’ focus was to analyze users’ moods when faced with different accessibility barriers. Results show “complex text” and “multimedia content without text alternative” as the most critical barriers for users with this profile. Our investigation contributes to a better understanding of users when confronting accessibility barriers, and to emphasize the need of web content authors to use plain language and to provide captions and sign language alternatives in video content